DIGITAL LITERACY BASED ON LOCAL WISDOM IN INCLUSIVE EDUCATION - Munisa Munisa; Utami Nurhafsari Putri; Wina Viqa Sari; Nurul Aida Fitri (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
This study examines the role of digital literacy based on local wisdom in the context of inclusive education. Digital literacy is essential in modern education, especially in the current digital era. However, inclusive education, which encourages the participation of children with various special needs, often requires a more specific approach focused on local wisdom to achieve maximum success. This research discusses the concept of digital literacy, defines local wisdom, and outlines how integrating digital literacy based on local wisdom can support inclusive education. The results indicate that this approach can significantly enhance participation, learning, and the development of inclusive education.Keywords: digital literacy, local wisdom, inclusive education